Structural adjustment and employment issues in the Netherlands Antilles - Jong, Heiko S.R. de (ILO. PREALC Caribbean Office Port of SpainTT, 1991)
Looks briefly at current economic development; (un)employment data; structural adjustment measures in the mid-eighties; recent compensatory measures; and measures addressing unemployment.